Understanding of Maternal Health Status in Different Social Groups in India Using NFHS Data - Santosh Tamang; Uttam Kumar Sikder (SAGE Publishing, 2024)
Maternal health is a major public health concern in India. MMR of India has declined significantly but maternal health status has not much improved. The prevalence of anemia and low Body Mass Index (BMI) is more severe among the women belonging to the Scheduled Caste (SC) and Scheduled Tribe (ST) categories. In this paper, attempts have been made to examine the maternal health status and to identify the factors responsible for poor health status among SC and ST women. The study is purely based on secondary data taken from latest 3 rounds of NFHS (2005-6, 2015-16 & 2019-21). Multivariate analysis have been carried out using panel regression model to understand the impact of determinants on maternal healthcare. The study found that the SC and ST women are more prone to anemia than others (GENERAL category women). Maternal health status is mostly controlled by per capita health expenditure and health infrastructure variables like no. of hospitals and nurses, irrespective of social class. Thus poor maternal health status in India, especially among socially disadvantaged groups of society, have been major concern. The government should be more focused on existing policies related to maternal healthcare.